2010
DOI: 10.1149/1.3358145
|View full text |Cite
|
Sign up to set email alerts
|

Highly (111) Textured Copper Foils with High Hardness and High Electrical Conductivity by Pulse Reverse Electrodeposition

Abstract: The present article reports the pulse reverse electrodeposition of highly ͑111͒ textured freestanding copper foils, in an additive-free electrolyte, exhibiting hardness as high as 2.2-2.7 GPa with an electrical conductivity equal to that of bulk copper. The short anodic pulse applied and the absence of organic additives allowed the formation of highly dense foils with room-temperature stability in terms of mechanical and electrical properties. The process involves a fast electrodeposition method with a deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…During the deposition, development of (111) texture is also favored at large current densities applied at low temperatures due to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 minimization of the surface/interfacial energy during growth process. Our previous study has also revealed that (111) texture is favorable at high current densities with short forward pulses and short reverse pulses 31 . In addition, low deposition temperatures are suggested in order to minimize the surface and interfacial energies, for twin boundary formation, good surface properties and to reduce the usage of additives 67 .…”
Section: Texture Validation By Ebsd and Xrdmentioning
confidence: 77%
See 3 more Smart Citations
“…During the deposition, development of (111) texture is also favored at large current densities applied at low temperatures due to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 minimization of the surface/interfacial energy during growth process. Our previous study has also revealed that (111) texture is favorable at high current densities with short forward pulses and short reverse pulses 31 . In addition, low deposition temperatures are suggested in order to minimize the surface and interfacial energies, for twin boundary formation, good surface properties and to reduce the usage of additives 67 .…”
Section: Texture Validation By Ebsd and Xrdmentioning
confidence: 77%
“…In order to evaluate this, the copper foils are stored at room temperature for six months. Subsequently hardness of these foils was measured and it was found that the hardness has decreased by only 5% in comparison to its as-deposited value 31 . This constancy of hardness at room temperature is probably due to the absence of grain growth 68 .…”
Section: Mechanical and Electrical Properties Of The Highly Textured mentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the 35-µm-thick R-Cu CC foil shows a texture-like structure formed along a certain direction because it only has a strong peak in the (220) plane. According to the results of Sarada et al 24 , the foils with a strong peak in the (111) plane had high electrical conductivity, which is the key factor for use as CC in LIBs. This may be a reason why most commercial industries often select E-Cu foils and not R-Cu foils for anode CCs.…”
Section: Yield Strength and Fracture Strengthmentioning
confidence: 99%